The use of acoustic streaming in Sub-micron particle sorting. Issue 3 (26th January 2022) - Lai, Tsz Wai; Fu, Sau Chung; Chan, Ka Chung; Chao, Christopher Y. H.
Abstract: The lack of personal particulate matter (PM) monitoring technique hinders the knowledge of the negative health impacts caused by inhaling PM. Acoustophoresis has a potential to produce miniature particle sorters that can be carried inside human's breath zone. Micron particles can be manipulated by Acoustic Radiation Force (ARF), but sub-micron particles can hardly be directed due to Acoustic Streaming Effect (ASE). The purpose of this study is to examine the feasibility of sorting sub-micron particles using ASE. In this study, a 2 D numerical model is used to simulate the movement of sub-micron particles, ranging from 0.1 µm to 0.9 µm in diameter with 0.1 µm step size, suspended in a microchannel. Since tiny particles circulate according to the streaming pattern, which depends on the geometry of the container, the effect of the microchannel's cross-sectional shape on particle movement is investigated, from rectangular to non-rectangular. Results found that sub-micron particles are characterized as either ARF-dominant or ASE-dominant. ARF-dominant particles stop at the pressure node and sidewalls, while ASE-dominant particles are trapped by the streaming flow inside a certain area defined by the particle size. Larger ASE-dominant particles move in a narrower region close to the sidewalls; smaller particles occupy a wider area. Since ASE-dominant particles can be directed outside the settling location of ARF-dominated particles, separating them can reach 98.9% purity in a non-rectangular microchannel. Most importantly, separating ASE-dominant particles of different sizes is shown possible using a triangular microchannel. The findings imply that ASE can be the mechanism for sub-micron particle sorting. Copyright © 2021 American Association for Aerosol Research